ENGINEERING PROTECTION ECO-SYSTEMS TERRITORIES ON THE BIOSPHERE COMPATIBILITY PRINCIPLES APPLICATION - Chernyshev, D. O. (Academic journal Industrial Machine Building Civil Engineering, 2017)
The article is devoted to the solution of the actual scientific and applied problem issue - the search for organizational and technological solutions for biosferous construction on  the example of marine and river coastal areas engineering protection in Ukraine. The main causes of imperfect activities in the field of coastal areas protection are: insufficient considering natural processes laws in the coastal zone of sea, reservoirs and rivers during the formation of design decisions; work incompleteness andcoastal protection and coastal regulating structures formation incompleteness in local complexes that fully cover coastal natural systems where there is a high level of natural processes interconnections that do not ensure their project effectiveness. It was substantiated that objective of shores engineering protection ecosystems increasing objective reliability is the most rational damaging construction of the gabions.
Keywords: technological processes; вiospherе compatibility; оrganizational and technological solutions; сonstruction production